Pengaruh Program Revolusi Hijau Terhadap Kualitas Lahan Rawa Pertanian di Desa Sarang Lang Tahun 1972-1973 - Zahrani, Sahrin; Putri, Devin Jane; Maharani, Aulia; Safitri, Sani; Oktapiani, Rani (Jurnal Pendidikan Sejarah, 2025)
This research aims to determine the impact of the green revolution development program in Sarang Lang Village on the community, especially in the economic and social fields. Initially, this program wanted to increase the efficiency of community agricultural land by opening swamp land for irrigation so that the productivity of the agricultural sector could increase, but the lack of government management and operations in managing this program had a negative impact on the condition of agricultural land which affected the quality of the harvest. Researchers applied field study methods to determine the background and phenomena that occurred as well as geographical analysis to determine the condition of swamp land in Sarang Lang Village. It is hoped that this research can help provide information to readers regarding the influence that the green revolution development program has had on the community’s economy.